The Challenge of Protein Crops as a Sustainable Source of Food and Feed for the Future - Francesca Sparvoli (Frontiers Research Topics, 2017)
Grain legumes, together with quinoa and amaranth (pseudocereals) and other crops are attractive candidates to satisfy the growing demand for plant protein production worldwide for food and feed. Despite their high value, many protein crops have not been adequately assessed and numerous species are underutilized. Special attention has to be paid to genetic diversity and landraces, and to the key limiting factors affecting yield, including water deficiency and other abiotic and biotic stresses, in order to obtain stable, reliable and sustainable crop production through the introduction and local adaptation of genetically improved varieties. Legumes, the main protein crops worldwide, contribute to the sustainable improvement of the environment due to their ability to fix nitrogen and their beneficial effects on the soil. They play a key role in the crop diversification and sustainable intensification of agriculture, particularly in light of new and urgent challenges, such as climate change and food security. In addition, the role of legumes in nutrition has been recognized as a relevant source of plant protein, together with other benefits for health. Chapters dealing with common bean, lupine, soybean, lentil, cowpea and Medicago are included in this book. Most contributions deal with legumes, but the significant number of papers on different aspects of quinoa gives an idea of the increasing importance of this protein crop. Pseudocereals, such as quinoa and amaranth, are good sources of proteins. Quinoa and amaranth seeds contain lysine, an essential amino acid that is limited in other grains. Nutritional evaluations of quinoa indicate that it constitutes a source of complete protein with a good balance among all of the amino acids needed for human diet, and also important minerals, vitamins, high quality oils and flavonoids. Other protein crops also included in this book are hemp, cotton and cereals (maize, wheat and rice). Although cereals protein content is not high, their seeds are largely used for human consumption. In this book are included articles dealing with all different aspects of protein crops, including nutritional value, breeding, genetic diversity, biotic and abiotic stress, cropping systems or omics, which may be considered crucial to help provide the plant proteins of the future. Overall, the participation of 169 authors in 29 chapters in this book indicates an active scientific community in the field, which appears to be an encouraging reflect of the global awareness of the need for sustainability and the promising future of proteins crops as a source of food and feed.